AI-Powered CALL and L2 Pragmatic Competence Development among Indonesian EFL Learners - Cecep Agus; Astri Dwi Floranti (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This research examines whether using AI-generated feedback enhances learners' pragmatic competence and how they engage with intelligent feedback during task-based communication. The study employed an explanatory sequential mixed-methods design with 60 undergraduate EFL students divided into experimental and control groups over eight weeks. Results indicated that learners in the experimental group significantly outperformed learners in the control group in the pragmatically appropriate use of language, politeness strategies and contextually appropriate use of language. Additionally, the analysis showed that immediate and adaptive AI-generated feedback led learners to notice their mistakes, self-repair, and repeat their revisions in cycles. Qualitatively, learners described the AI environment as supportive, flexible, and less anxiety-inducing, which helped them feel more confident in their language use. This study also shows how AI-powered CALL environments can help learners develop L2 pragmatic competence by providing personalized, interactive feedback. Finally, these findings describe the pedagogical possibilities of intelligent feedback systems within a systematically designed instructional approach to support pragmatic instruction in EFL contexts.